2022
DOI: 10.1136/bmjopen-2021-052193
|View full text |Cite
|
Sign up to set email alerts
|

Association between sleep duration and hypertension in southwest China: a population-based cross-sectional study

Abstract: ObjectiveHypertension is a major risk factor and cause of many non-communicable diseases in China. While there have been studies on various diet and lifestyle risk factors, we do not know whether sleep duration has an association to blood pressure in southwest China. This predictor is useful in low-resource rural settings. We examined the association between sleep duration and hypertension in southwest China.DesignPopulation-based cross-sectional study.SettingThis study was part of the baseline survey of a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Third, a disordered sleep duration can lead to high blood pressure, which may further damage the kidneys. A study from China discovered that long sleep duration was signi cantly associated with hypertension; however, this association was not obvious between short sleep duration and hypertension [30] . He et al found that a short sleep duration was related to an increased risk of hypertension [31] .…”
Section: Discussionmentioning
confidence: 99%
“…Third, a disordered sleep duration can lead to high blood pressure, which may further damage the kidneys. A study from China discovered that long sleep duration was signi cantly associated with hypertension; however, this association was not obvious between short sleep duration and hypertension [30] . He et al found that a short sleep duration was related to an increased risk of hypertension [31] .…”
Section: Discussionmentioning
confidence: 99%
“…It is often described as a “silent killer” because it rarely causes symptoms ( 49 ). Currently, studies prove a significant association between short sleep (less than 5 hours per night) and an increased risk of hypertension ( 19 , 50 ). In the Penn State Cohort study, Bertisch et al.…”
Section: Main Textmentioning
confidence: 99%